Surface‐Confined SnS2@C@rGO as High‐Performance Anode Materials for Sodium‐ and Potassium‐Ion Batteries. Issue 12 (15th May 2019) - Li, Deping; Sun, Qing; Zhang, Yamin; Chen, Lina; Wang, Zhongpu; Liang, Zhen; Si, Pengchao; Ci, Lijie
Abstract: Potassium‐ (PIBs) and sodium‐ion batteries (SIBs) are emerging as promising alternatives to lithium‐ion batteries owing to the low cost and abundance of K and Na resources. However, the large radius of K + and Na + lead to sluggish kinetics and relatively large volume variations. Herein, a surface‐confined strategy is developed to restrain SnS2 in self‐generated hierarchically porous carbon networks with an in situ reduced graphene oxide (rGO) shell (SnS2 @C@rGO). The as‐prepared SnS2 @C@rGO electrode delivers high reversible capacity (721.9 mAh g −1 at 0.05 A g −1 ) and superior rate capability (397.4 mAh g −1 at 2.0 A g −1 ) as the anode material of SIB. Furthermore, a reversible capacity of 499.4 mAh g −1 (0.05 A g −1 ) and a cycling stability with 298.1 mAh g −1 after 500 cycles at a current density of 0.5 A g −1 were achieved in PIBs, surpassing most of the reported non‐carbonaceous anode materials. Additionally, the electrochemical reactions between SnS2 and K + were investigated and elucidated. Abstract : Building better batteries : A surface‐confining strategy is proposed to prepare dual carbon‐coated SnS2 @C@rGO composite as electrode material. Benefiting from the unique structure, the as‐prepared electrode exhibits high reversible capacity and superior rate capability in both sodium‐ and potassium‐ion batteries. This work provides a strategy for designing better anode materials and sheds light on the research of alternatives to lithium‐ion batteries.